Learning of Children with Special Needs in Inclusive Schools - Ria Arianti; Sowiyah Sowiyah; Handoko Handoko; Riswanti Rini (International Journal Labs, 2022)
Background: Inclusion schools are educational services provided to children with special needs in obtaining a proper education. In the implementation of inclusive schools, children with special needs learn together with normal children and are served like normal children and treated like normal children. Objective: The purpose of this literature review is to find out how children with special needs learn in inclusive schools. Method: The research method used is a literature review by looking at various literature on the learning process, children with special needs, and inclusion schools Results: The results of the literature review show that the learning of children with special needs in schools is carried out by teachers with sufficient competence to serve children with special needs and normal children at one time. Teachers understand the characteristics in the form of the nature of students' strengths and weaknesses with various learning strategies and methods. Conclusion: Inclusion schools are organized as regular schools, but accept children with special needs as learners by providing a system of educational services tailored to the needs of both normal learners and students with special needs through curriculum adjustments, strategies or learning methods, assessment, and preparation of infrastructure.